The Routledge handbook of the political economy of health and healthcare - Primrose, David; Loeppky, Rodney, 1969-; Chang, Robin (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This handbook provides a comprehensive and critical overview of the gamut of contemporary issues around health and healthcare from a political economy perspective. Its contributions present a unique challenge to prevailing economic accounts of health and healthcare, which narrowly focus on individual behaviour and market processes. Instead, the capacity of the human body to reach its full potential, and the ability of society to prevent disease and cure illness, are demonstrated to be shaped by a broader array of political economic processes. The material conditions in which societies produce, distribute, exchange, consume, and reproduce - and the operation of power relations therein - influence all elements of human health: from food consumption and workplace safety, to inequality, healthcare and housing, and even the biophysical conditions in which humans live. The volume explores these concerns across five sections. First, it introduces and critically engages with a variety of established and cutting-edge theoretical perspectives in political economy to conceptualise health and healthcare - from neoclassical and behavioural economics, to Marxist and feminist approaches. The next two sections extend these insights to evaluate the neoliberalisation of health and healthcare over the past forty years, highlighting their individualisation and commodification by the capitalist state and powerful corporations. The fourth section examines the diverse manifestation of these dynamics across a range of geographical contexts. The volume concludes with a section devoted to outlining more progressive health and healthcare arrangements, which transcend the limitations of both neoliberalism and capitalism. This volume will be an indispensable reference work for students and scholars of political economy, health policy and politics, health economics, health geography, the sociology of health, and other health-related disciplines"--
Keywords: Politics, Practical; Medical economics; BUSINESS & ECONOMICS / Economics / Microeconomics; BUSINESS & ECONOMICS / Economics / General